2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00962
|View full text |Cite
|
Sign up to set email alerts
|

SBSGAN: Suppression of Inter-Domain Background Shift for Person Re-Identification

Abstract: Cross-domain person re-identification (re-ID) is challenging due to the bias between training and testing domains. We observe that if backgrounds in the training and testing datasets are very different, it dramatically introduces difficulties to extract robust pedestrian features, and thus compromises the cross-domain person re-ID performance. In this paper, we formulate such problems as a background shift problem. A Suppression of Background Shift Generative Adversarial Network (SBSGAN) is proposed to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…As DBC also predicts labels via unsupervised clustering, these results indicate that proposed GLO method can effectively improve the discriminative ability of learned features. It can also be observed that GLO also outperforms several domain adaptive methods such as PAUL [45] and DA_2S [14]. Specially, compared with ECN [60] that uses a source dataset, GLO still outperforms it by 2.7% in mAP on Market-1501.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…As DBC also predicts labels via unsupervised clustering, these results indicate that proposed GLO method can effectively improve the discriminative ability of learned features. It can also be observed that GLO also outperforms several domain adaptive methods such as PAUL [45] and DA_2S [14]. Specially, compared with ECN [60] that uses a source dataset, GLO still outperforms it by 2.7% in mAP on Market-1501.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 83%
“…Our method achieves Rank-1 accuracy of 77.4% on Market-1501, significantly outperforming recent BUC [25] and DBC [6] by 11.2% and 8.2%, respectively. It is worth noting that, our unsupervised training also outperforms several domain adaptive methods that use extra source domain for training, such as PAUL [45] and DA_2S [14].…”
Section: Figure 1: Illustration Of Proposed Coupling Optimization Metmentioning
confidence: 85%
See 3 more Smart Citations